HUBUNGAN ANTARA PENGGUNAAN SHOULDER BAG DENGAN KEJADIAN TRAPEZIUS MYALGIA - Ramadhini, Amira Alya Cendekia; Adji, Raden Mas Soerjo; Kesoema, Tanti Ajoe; Wajdi, Muhammad (Medica Hospitalia : Journal of Clinical Medicine, 2022)
Background : The prevalence of Trapezius Myalgia is increasing, specifically in productive age (15-64 years old). In Indonesia, Trapezius Myalgia cases are less identified due to its minimal publication and frequently underdiagnosed. Trapezius Myalgia is generated by anaerobic metabolism in trapezius muscle triggered by lack of oxygenation. This process would release pain mediators and perceived as pain. Some factors were believed to cause trapezius myalgia, such as gender, heavy loads, repetitive movement, postures, and working with computer. The use of shoulder bag is considered as static loading and repetitively performed which is believed to cause trapezius myalgia. Aim : To determine the association between shoulder bag usage with Trapezius Myalgia in Toko Ananda Pojok Semarang workers. Method : This was an observational analytic study with cross-sectional design. Data assembled was primary data, consist of Nordic Musculoskeletal Questionnaire (NMQ) and confirmed by palpation using manual algometer. A total of 54 workers in Toko Ananda Pojok were selected as subjects. The group consists of 30 shoulder bag user and 24 non-shoulder bag user. Pearson Chi-Square was used for statistical analysis Results : Based on NMQ results, 30 subjects (55,6%) had neck pain, 35 subjects (64,8) had shoulder pain, 30 subjects (55,6%) had upper trapezius pain, and 20 subjects (37%) had lower trapezius pain. Pearson Chi-Square test of shoulder bag (p = 0,036) was statistically significant for trapezius myalgia risk (p<0,05). Conclusion : There was an association between shoulder bag usage with trapezius myalgia.